H24

Tìm x: (x - 2)(x + 2) - (x + 3)(x- 3x+ 9) = 6x - 27

LD
3 tháng 9 2020 lúc 6:40

( x - 2 )( x + 2 ) - ( x + 3 )( x2 - 3x + 9 ) = 6x - 27

<=> x2 - 4 - ( x3 + 27 ) = 6x - 27

<=> x2 - 4 - x3 - 27 = 6x - 27

<=> x2 - 4 - x3 - 27 - 6x + 27 = 0

<=> -x3 + x2 - 6x - 4 = 0

Gồi đến đây là chịu :)

Bình luận (0)
 Khách vãng lai đã xóa

Các câu hỏi tương tự
CM
Xem chi tiết
PB
Xem chi tiết
TM
Xem chi tiết
HH
Xem chi tiết
LD
Xem chi tiết
PB
Xem chi tiết
PA
Xem chi tiết
IC
Xem chi tiết
TL
Xem chi tiết